Past behaviours and future intentions: An examination of perceptual deterrence and alcohol consumption upon a range of drink driving events. (March 2020) - Freeman, James; Parkes, Alexander; Lewis, Naomi; Davey, Jeremy D.; Armstrong, Kerry A.; Truelove, Verity
Highlights: Various measures used to operationalise drink driving were examined. Perceptions of both legal and non-legal sanctions for drink driving were high. Non-legal sanctions were a larger deterrent for drink driving than legal sanctions. Past drink-driving conviction was a predictor of re-offending. Age, gender and risky drinking behaviours were drink driving predictors. Abstract: Introduction: The threat of application of legal sanctions remains the prominent approach to reduce the prevalence of drink driving in a vast array of motoring jurisdictions. However, ongoing questions remain regarding: (a) the extent that such mechanisms impact upon offending behaviours, (b) the deleterious effect alcohol consumption has on decisions to drink and drive and (c) how best to operationalise (and measure) the concept of drink driving to enhance the accurate measurement of the dependent variable. Method: This paper reports on an examination of 773 Queensland motorists' (across nine local government areas) perceptions of both legal and non-legal drink driving sanctions (as well as alcohol consumption) in order to gauge the deterrent impact upon a range of measures of drink driving: the driver thinking they are over the limit, the driver knowing they are over the limit, attempts to evade random breath testing, and intentions to re-offend. The sample completed an online or paper version of the questionnaire. Results: The majority of participants reported "never" engaging in "possible" (74.5 %) or "acknowledged" (83.4 %) drink driving events, although a considerable proportion of the sample reported engaging in "possible" (25.5 %) or "acknowledged" (16.6 %) drink driving and attempting to evade RBT (18 %) events, as well as possible intentions to drink and drive in the future (22 %). Males were more likely to report such events. Perceptions of both legal sanctions (certainty, severity and swiftness) as well as non-legal sanctions (fear of social, internal or physical harm) were relatively high and consistent with previous research. Interestingly, non-legal sanctions were reported as stronger deterrents than legal sanctions. However, multivariate analysis revealed that legal deterrents had limited utility predicting offending behaviours, but rather, demographic characteristics (e.g., younger motorists, males) as well as risky drinking behaviour were better predictors. In regards to intentions to offend, a past conviction for drink driving was also a predictor of re-offending. Practical applications: These results highlight the ongoing challenges of addressing the problem of drink driving and that some motorists: (a) have entrenched behaviour and/or (b) make the decision to drink and drive before they are under the influence of alcohol.